Decreasing in Blood Pressure with Music Therapy (Vivaldi-The Four Season) in Elderly Patients With Hypertension in PSTW Glenmore Banyuwangi - Rahmawati Raharjo; Agung Dwi Rahardjo (Fakultas Ilmu Kesehatan, 2020)
The elderly is a vulnerable age group having health problems. The addition of age causes the function and structure of organs, especially the cardiovascular system and blood vessels, the condition contributes to the trigger occurs an increase in blood pressure. Prevention and management of hypertension can be done by pharmacological and non-pharmacological methods. The non-pharmacological method that can be intervened is classical music. The purpose of this study was to determine the effect of music therapy on reducing blood pressure in hypertensive elderly. This type of research design uses a pre-experimental design with one group pre-test-post test design approach. Samples were taken using a purposive sampling technique of 53 elderly people living in the Banyuwangi Tresna Werdha Social Home. Analysis of data using the Wilcoxon test with a value of p <0.05. Wilcoxon analysis test results obtained p or (Asymp. Sig. (2-tailed) = 0,000, p <0.05. These results research showed there was a difference before and after given classical music therapy in elderly patients with hypertension. Then it can be concluded that the delivery of music therapy in patients with hypertension will help in lowering blood pressure so that music therapy (Vivaldi-the four-season) becomes a non-pharmacological solution both in service and self-handling.